PEMANFAATAN PERBANDINGAN HUKUM DALAM PEMBANGUNAN SISTEM HUKUM NASIONAL (Suatu Kajian Terhadap Sistem Hukum Waris Indonesia) - Suswoto Suswoto (Kajian Hukum, 2020)
Law development is one of the vital activities in a country, not excluding our country, because it has never left the wheel of universal development that is currently being promoted in all elements of the development community. In our country which embraces pluralism, the policy taken in dealing with the various sources of law is open. This is none other than a logical consequence of the Pancasila Law Order itself which is more of an open ideology. Therefore, the existing legal sources in Indonesia will be accepted and used as far as the material is in accordance with the legal needs of the Indonesian people. On this basis, then in compiling a new legal system in Indonesia can be used materials such as customary law, Islamic law, and western law that already exists in Indonesia. It is even open to the possibility of using materials sourced from foreign countries that were previously unknown as long as they are not contrary to the philosophy of Pancasila, as a national policy or even its basic norm. Based on the above background, the author focuses the discussion of the article on the issues, namely; how to utilize legal comparisons in the development of inheritance law in Indonesia, especially in relation to successor heirs. Keywords : comparative law, inheritance law, law of development.